2016
DOI: 10.2116/analsci.32.371
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Automated Device for Purifying Nucleic Acids

Abstract: We have developed a rapid, automated nucleic acid purification device in a single cartridge containing silica-coated magnetic beads. We succeeded in extracting the matrix protein gene of influenza A virus from pharyngeal swab samples within 3 min. The device will be widely applicable to detect a specific gene from the various samples for clinical diagnosis and genetic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Over the last ten years, with the advent of isothermal amplification technologies (2), a new area of research has opened, raising hope to perform NAATs at the point of care, with portable devices much cheaper than extraction/PCR platforms and showing comparable performances. A new generation of NAATs has grown along the years, in laboratories, often coupling isothermal amplification to paper microfluidics, a field pioneered by G.Whitesides (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last ten years, with the advent of isothermal amplification technologies (2), a new area of research has opened, raising hope to perform NAATs at the point of care, with portable devices much cheaper than extraction/PCR platforms and showing comparable performances. A new generation of NAATs has grown along the years, in laboratories, often coupling isothermal amplification to paper microfluidics, a field pioneered by G.Whitesides (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…2c). 9 The pushing system controls the cartridge plunger and pushes the reaction solution plug and oil plug into the PCR tube (Figs. 3a, 3b, and 3c).…”
Section: Device Constructionmentioning
confidence: 99%
“…We used a transport speed of 2.0 mm s -1 and a vibration frequency of 4.0 Hz. 9 Nucleic acids bound to the magnetic beads are thus washed into the washing solution and eluted in the reaction solution (Fig. 2b).…”
Section: Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our lab [20, 21] and others [22–27] have shown that instead of pipetting liquids in and out of a tube that contains the PMPs, there is an advantage to using stationary microfluidics whereby different buffers needed for extraction are located in fixed positions, and an external magnet transfers the PMPs between the fluids through an immiscible phase filter (IPF) made up of a layer of oil or liquid wax that is immiscible with both aqueous solutions. In addition to eliminating the need for fluid pumping or pipetting, moving PMPs instead of fluids simplifies the instrumentation and consumable test cartridge required for nucleic acid extraction.…”
Section: Introductionmentioning
confidence: 99%